The Place of Socio-Political Speech Among Other Types - Nurmanova Salomat Tursinbayevna (Genius Journals, 2022)
The article talks about the history of oratory, socio-political oratory and its types.
Keywords: Oratory; preacher; political speech; reporting speech; propaganda speech